MANFAAT KESEHATAN BAKTERI ASAM LAKTAT - Purwandhani, Siti Nur (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2017)
Lactic acid bacteria has potential as health-supporting agent because of its role as probiotic that has capability to grow in gastrointestinal tract, and its metabolites/cell components that have health benefits. Health benefits of lactic acid bacteria include balancing intestinal microflora so it can play a role in treating diarrhea, preventing cancer, lowering serum cholesterol, treating lactose intolerant, and preventing constipation. In terms of nutritional value, lactic acid bacteria is capable of increasing the biological value of milk protein, synthesizing vitamin B, inhibiting antinutrient compound, inhibiting toxins production, and producing antimicrobial substances. Examples of lactic acid bacteria strain that can be used as a probiotic are Lactobacillus reuteri, Lactobacillus acidophilus, Lactobacillus plantarum and Lactobacillus casei.